2022
DOI: 10.3390/atmos14010008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil Moisture-Based Satellite Precipitation Products over Semi-Arid Climatic Region

Abstract: The ground validation of satellite-based precipitation products (SPPs) is very important for their hydroclimatic application. This study evaluated the performance assessment of four soil moisture-based SPPs (SM2Rain, SM2Rain- ASCAT, SM2Rain-CCI, and GPM-SM2Rain). All data of SPPs were compared with 64 weather stations in Pakistan from January 2005 to December 2020. All SPPs estimations were evaluated on daily, monthly, seasonal, and yearly scales, over the whole spatial domain, and at point-to-pixel scale. Wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…The ground validation demonstrates that, at a monthly scale, all SBPPs, SBTPs, and TRPs exhibit better agreement with in-situ gauge estimations, corroborating the outcomes of numerous previous studies. For example, Anjum et al (2016) found that CHIRPS-2.0 and SM2Rain-ASCAT precipitation products effectively represent the spatial distribution of precipitation over most parts of Pakistan, a result also supported by Asif et al (2023) and Nadeem et al (2022) in their investigations of spatial abilities. At the daily scale, the linear agreement between the reference data and the estimations of all SBPPs was found to be poor, as indicated by low correlation coe cient values.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The ground validation demonstrates that, at a monthly scale, all SBPPs, SBTPs, and TRPs exhibit better agreement with in-situ gauge estimations, corroborating the outcomes of numerous previous studies. For example, Anjum et al (2016) found that CHIRPS-2.0 and SM2Rain-ASCAT precipitation products effectively represent the spatial distribution of precipitation over most parts of Pakistan, a result also supported by Asif et al (2023) and Nadeem et al (2022) in their investigations of spatial abilities. At the daily scale, the linear agreement between the reference data and the estimations of all SBPPs was found to be poor, as indicated by low correlation coe cient values.…”
Section: Discussionmentioning
confidence: 92%
“…The in uence of local topography and meteorological factors on the performance of these products has been widely recognized. Previous studies by Asif et al (2023) and Nadeem et al (2022bNadeem et al ( , 2022a examined various satellite and reanalysis products and found that regional climatology and precipitation retrieval techniques signi cantly affect the accuracy of precipitation products. Similarly, Hamza et al (2020) compared the performance of SM2Rain and PERSIANN products and noted that evaluation indices such as RMSE and Bias were highly dependent on in-situ climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the low correlation coefficient values, the performance of all GPDS was very poor in comparison to gauge estimations, indicating the better agreement between the GPDS and the reference datasets on a monthly scale as compare to daily. According to [33,37], the estimations of GPM and CHIRPS calculations with the monthly data of the in situ stations were >0.70, showing the superior linear connections of their monthly observations. Moreover, the algorithm used, the data sources used as input, and the spatial and temporal resolution can all affect how well a precipitation estimator performs.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, only that region is affected by the amount of precipitation recorded at pixel I. Each pixel's weight depends on the region of the Thiessen polygon to which it belongs, following the methodology of [37]. For the performance analysis of GPDS in accordance with the WMO (World Meteorological Organization conventions), the standards for daily precipitation scales for low (2 mm/day), medium (>10 mm/day), and heavy precipitation were (>10 mm/day) used [27].…”
Section: Methodsmentioning
confidence: 99%